Berlin . Berlin - Yuli Raizman and Yelizaveta Svilova (Central Documentary Films Studio, 1945)
The film is interspersed with German newsreel shots narrating the Nazis' plan of global hegemony. The documentary describes the final major battle of the war with Nazi Germany, with its outcome, the German army's unconditional surrender. This film alongside other Soviet ones were shown in Cannes immediately after the end of the war. Film from the private archives of Nazi advisor Goebbels is used to bridge the history line between Mussolini, Hitler, and the emerging fascist movement in the 1960s among both East and West Germans.